Spirituality through the Images of Nature in "November Day at Mc Clure" (NOBEL: Journal of Literature and Language Teaching, 2015)
The analysis focuses on revealing spirituality through images of nature in Robert Bly's poem, "November Day at McClure". The purpose of the study is to depict the kinds of images of nature used and the spirituality reflection in the poem. To complete the analysis, concept of nature classification by Coleman J. Goin and Oliver B. Goin is applied. Based on the concept, there are some groups of images of nature: landscape, phenomenon, animal, plant, object above the earth, and other nature object. The analysis result shows the images of nature in the poem consist of some kinds such as: landscape, animal, phenomenon, object above the earth, and other nature object. Based on the concept of Ary Ginanjar Agustian, there are some kinds of spiritual reflection: through messages of loving unconditionaly, awaring fate and God, responsibility, time perspective, and being free from material things. The analysis result shows that the spirituality can be reflected through the message of awaring fate and God and message of responsibility.